Physical and emotional well-being and support in newly diagnosed head and neck cancer patient–caregiver dyads. Issue 6 (2nd November 2017) - Sterba, Katherine R.; Zapka, Jane; Armeson, Kent E.; Shirai, Keisuke; Buchanan, Amy; Day, Terry A.; Alberg, Anthony J.
ABSTRACT: The purpose of this study was to examine the physical and emotional well-being and social support in newly diagnosed head and neck cancer (HNC) patients and caregivers and identify sociodemographic, clinical, and behavioral risk factors associated with compromised well-being in patients and caregivers. Newly diagnosed HNC patients and their primary caregivers ( N = 72 dyads) completed questionnaires before treatment assessing physical and mental well-being, depression, cancer worry, and open-ended support questions. Patients reported worse physical well-being than caregivers ( p < 0.05) but similar levels of mental well-being. Caregivers reported providing emotional and instrumental support most frequently with an emphasis on nutrition and assistance with speech, appearance, and addictions. Both patients and their caregivers reported suboptimal mental well-being and depression. Smoking was associated with compromised well-being in patients, caregivers, and dyads. Compromised well-being in patients and their caregivers was more likely when patients were younger, had worse symptoms, and smoked/consumed alcohol ( p < 0.05). While patients face more physical strain than caregivers, both equally confront emotional challenges. Results highlight risk factors for compromised well-being in both patients and their caregivers that should be assessed at diagnosis to guide identification of needed dyadic-focused supportive care resources.